2016
DOI: 10.1007/s00418-016-1528-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of levamisole, acetylsalicylic acid, and α-tocopherol against dioxin toxicity measured as the expression of AhR and COX-2 in a chicken embryo model

Abstract: Polychlorinated dibenzo-p-dioxins and dibenzofurans (dioxins) are classed as persistent organic pollutants and have adverse effects on multiple functions within the body. Dioxins are known carcinogens, immunotoxins, and teratogens. Dioxins are transformed in vivo, and interactions between the products and the aryl hydrocarbon receptor (AhR) lead to the formation of proinflammatory and toxic metabolites. The aim of this study was to determine whether α-tocopherol (vitamin E), acetylsalicylic acid (ASA), and lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Hilscherova and others (Hilscherova et al, 2003) had found that dioxins cause oxidative DNA damage in chicken embryo livers by increasing the amounts of reactive oxygen species produced and depleting glutathione. In a study conducted by Gostomska-Pampuch and others (Gostomska-Pampuch et al, 2017), TCDD and α-tocopherol caused delayed liver development. In our study, the retarded growth of the liver may explain the statistically nonsignificant and small increase in the iron content in all experimental groups.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Hilscherova and others (Hilscherova et al, 2003) had found that dioxins cause oxidative DNA damage in chicken embryo livers by increasing the amounts of reactive oxygen species produced and depleting glutathione. In a study conducted by Gostomska-Pampuch and others (Gostomska-Pampuch et al, 2017), TCDD and α-tocopherol caused delayed liver development. In our study, the retarded growth of the liver may explain the statistically nonsignificant and small increase in the iron content in all experimental groups.…”
Section: Discussionmentioning
confidence: 91%
“…The authors would like to thank Prof. Ireneusz Całkosiński (1951Całkosiński ( -2017 for inspiration and helpful advice, as well as help with respect to organization and ensuring welfare of the animals.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,13,15,16 Dioxins which connect with the AhR cause a migration of the receptor into the cell nucleus, which induces the expression of genes for cytochromes. [17][18][19] Furthermore, dioxins have an affinity for the estrogen receptor and owing to this they contribute to reproductive disorders and behavioral disorders associated with the occurrence of changes in the expression of receptors in the central nervous system structures. 17 The most signicant documented adverse effects of dioxins include: chloracne, changes in the level of thyroid hormones with impairment of the psychomotor abilities, fertility problems or infertility, increased concentration of alpha-and betaglobulins and delayed immune response, and carcinogenic and teratogenic effects in humans.…”
Section: Introductionmentioning
confidence: 99%
“…3 The promising positive effects by tocopherol on structural and functional prevention of organs in the experimental intoxication by dioxins have prompted the authors to compare well known anti-inammatory and immunomodulating drugs on bone metabolism. [9][10][11][12][13] It was shown that administration of tocopherol or acetylsalicylic acid in mothers exposed to TCDD prevent decreases in calcium and magnesium concentrations in the calvaria of the offspring. 1 Moreover a protective effect of a low dose of a-tocopherol on Mg and Ca level in the bone of rat offspring aer intoxicating rat female rats with TCDD before insemination was evidenced.…”
Section: Introductionmentioning
confidence: 99%